Konsep Diri Remaja Kristen Yatim Piatu: Studi Fenomenologi - Kalis Stevanus; Maria Setiarini (Institut Agama Kristen Negeri Kupang, 2021)
The death of a parent can be a devastating and painful experience for a teenager. Teenagers lose love and parental figures. The correct self-concept is needed by teenagers in living their lives. To develop the correct self-concept, of course, involve other parties, such as orphanages. This study aims to describe the self-concept of adolescents who have orphaned status at the Dorkas Porong Orphanage, Sidoarjo. This study the author uses a qualitative approach with a phenomenological perspective. Data were collected through observation and in-depth interviews of the five research subjects who were orphans. The results showed that in general, they already had a good self-concept because of the Christian spiritual development at the orphanage. This spiritual guidance guides teenagers to learn to accept and appreciate themselves positively. They show: 1) a life style that is full of enthusiasm in carrying out daily life, 2) has a clear purpose in life, 3) can carry out daily responsibilities at the orphanage with enthusiasm and 4) is able to adapt to the environment. In addition, the formation of their self-concept supported by a family-friendly environment becomes a motivation for self-acceptance of adolescents and helps adolescents to live a normal adolescence, even without the presence of their parents.